Edukasi Anak-anak tentang Fenomena Gerhana dan Halo Matahari di Kota Pekanbaru - Utih Amartiwi (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
The decline in Indonesia's PISA scores for student science literacy in 2018 serves as an evaluation of our education system. Education in the 21st century needs to be designed differently from the previous system, as it demands the ability to compete globally and meet the challenges of the 2045 demographic bonus. To address this, the Ministry of Education and Culture (Kemendikbud) has introduced the concept of "Merdeka Belajar" (Freedom to Learn). One aspect of "Merdeka Belajar" is observing the phenomena that occur around us. On April 20, 2023, a solar eclipse occurred and could be witnessed in most parts of Indonesia. In the Pekanbaru region, the solar eclipse was even more captivating due to the simultaneous occurrence of a "Sun Halo" phenomenon. The author utilized this phenomenon to provide science education to the community, particularly children. Although many may not have a strong interest in science at school, this phenomenon sparked their curiosity to learn, think critically and skeptically, and understand causality in physics.